A narrative review of environmental noise and cardiovascular health: From molecular mechanisms to public health impact - Rahul Garg (Environmental Disease)
Urban environments of the 21st century present unprecedented challenges to human health, with environmental noise emerging as a critical determinant of cardiovascular well-being. This integrative analysis synthesizes contemporary understanding of noise-induced cardiovascular effects, incorporating insights from molecular biology, clinical research, and epidemiological investigations. The physiological response to noise encompasses both rapid adaptations and sustained modifications, including autonomic nervous system modulation, stress hormone cascades, and altered inflammatory pathways. Large-scale population studies demonstrate robust associations between chronic noise exposure and cardiovascular conditions, with particular emphasis on hypertension and coronary artery disease. The disruption of sleep architecture emerges as a central mechanism linking environmental noise to cardiovascular dysfunction. Vulnerability to these effects varies across populations, influenced by genetic, demographic, and preexisting health factors. Evidence supports a graded relationship between noise intensity and cardiovascular risk, suggesting a lack of safe threshold. These findings carry profound implications for urban planning and public health policy, highlighting the urgent need for innovative noise reduction strategies in modern living spaces.